Automatização de um teste de equilíbrio dinâmico e funcional: um estudo de desenvolvimento, acurácia e confiabilidade do AutomaSEBT - Souza, Gabriela dos Santos de (2024)
The development of innovations in the health field is important for scientific progress, meeting the demands of professionals and improving the standardization and reliability of physical tests. This thesis highlights the importance of creating technological solutions that facilitate the work of health professionals who work in the rehabilitation of dynamic postural balance disorders. This document includes a review of the relevant literature, two original studies and the registration of a computer program developed during the research. The main objective of this thesis was to develop and validate a prototype for measuring distances in the dynamic and functional balance test, known as the modified SEBT (SEBTm), with a focus on verifying its accuracy and reliability. The first original study involved the development of a prototype using a microcontroller and a laser-sensor, tested in different scenarios that varied range directions, target ranges, laser-sensor configurations and heights of the prototype in relation to the ground. Linear regressions were applied to correct the values estimated by the prototype, and Intraclass Correlation Coefficients (ICC) were calculated to validate these corrections. The second original study was an accuracy and reliability study with 30 participants (60 lower limbs), where the measurements of the new device, called AutomaSEBT, were compared simultaneously with the gold standard (VICON®) and the usual manual measurement, using Bland-Altman plots and ICC to analyze agreement and reliability between the methods. The results indicated that the prototype first showed systematic errors in specific scenarios, but after corrections using equations, it showed excellent reliability (r > 0.90; p < 0.001). In the AutomaSEBT test, reliability was excellent compared to the gold standard in the anterior (r ≥ 0.93), posteromedial (r ≥ 0.97) and posterolateral (r ≥ 0.99) directions. We conclude that the development of the AutomaSEBT has automated SEBTm measurements, offering healthcare professionals a new perspective for assessing dynamic postural balance. This reliable, low-cost device facilitates the assessment process and is effective in reducing the workload of examiners, increasing the standardization of physical tests and improving the repeatability of quantitative results. In this way, professionals who deal with patients with dynamic postural balance dysfunctions, such as physiotherapists, speech therapists, physical educators and doctors, will be able to use the SEBTm more easily and consistently, increasing the quality of clinical assessments.